Pembangkangan Sipil Umat Islam di Yogyakarta terhadap Sabda Raja - M. Rizal Qasim; Gugun El Guyanie (IN RIGHT: Jurnal Agama dan Hak Azazi Manusia, 2017)
This research is to investigate Muslim people movement at Yogyakarta who rejects Sabda Raja. Last year, Sri Sultan Hamengkubuwono, a King of Yogyakarta, established a new decree called by Sabda Raja. One of principal messages of the Sabda Raja is to allow a woman (princess) becomes a King/Queen. The Sabda Raja above immediately sparks for and contra among Yogyakarta people, including Muslim People. Several Muslim communities like NU and Muhammadiyah are against Sabda Raja. The reason Muslim people are using to reject Sabda Raja is that it breaks Kraton principle (Paugeran). The principle affirms that a King of Yogyakarta is a man, not woman. Several Muslim people at Yogyakarta considers that Sultan has an political ambition to establish his daughter (princess), GKR Pembayun, to be the next King (Queen) of Yogyakarta, because he does not have a son (prince). Sabda Raja is a legal tool to reach the ambition. Besides that, Sabda Raja also tends to remove religious degree, Khalifatullah, that is attached on King of Yogyakarta. Because of those reasons, Muslim people oppose Sabda Raja.